2020
DOI: 10.1109/jeds.2020.2986172
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation of an n-Type Tin-Oxide Thin Film Transistor by Channel Plasma Processing

Abstract: In this paper, we investigated the performance of an n-type tin-oxide (SnO x) thin film transistor (TFT) by experiments and simulation. The fabricated SnO x TFT device by oxygen plasma treatment on the channel exhibited n-type conduction with an on/off current ratio of 4.4x10 4 , a high field-effect mobility of 18.5 cm 2 /V.s and a threshold swing of 405 mV/decade, which could be attributed to the excess reacted oxygen incorporated to the channel to form the oxygen-rich n-type SnO x. Furthermore, a TCAD simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Hence, it restricts hole conduction. Although, there are various reports on the successful implementation DOS model of n-type a-IGZO TFTs [22], SnO2 base TFTs are rarely modeled [38]. Saji et al, successfully demonstrated the fabrication of SnO2 TFT [35] using RF sputtering.…”
Section: N-type Sno 2 Tftsmentioning
confidence: 99%
“…Hence, it restricts hole conduction. Although, there are various reports on the successful implementation DOS model of n-type a-IGZO TFTs [22], SnO2 base TFTs are rarely modeled [38]. Saji et al, successfully demonstrated the fabrication of SnO2 TFT [35] using RF sputtering.…”
Section: N-type Sno 2 Tftsmentioning
confidence: 99%